Don't let the little man live in your head for free: an interpretive phenomenological analysis of seafarers with reportedly high levels of well-being - Brown, Lauren Natalie (Rhodes University, Faculty of Humanities, Department of Psychology)
The mental health of seafarers has become a growing issue of concern and has attracted the attention of researchers in recent times. Seafarers are predominantly men, spend months at sea with little to no contact with loved ones ashore, and usually must reside in confined spaces that often contain substantial levels of noise and heat. The underlying causes of mental illness among seafarers are known. Some of the causes include sleep deprivation, occupational stress, marital/relationship problems, fatigue, the threat of piracy, psychosocial workload, loneliness, social isolation, separation from families, lack of shore leave, cultural issues, and job security. Despite these stressors, there are many men and women seafarers who flourish in the industry and enjoy their careers. Very little research has been conducted into the well-being practices of those seafarers who enjoy high levels of well-being. This study explores the lived experiences of a group of seafarers with reportedly high levels of psychological well-being, as well as their experiences of workplace stressors and mental health interventions offered by the industry. This study is an interpretive phenomenological analysis, which is epistemologically underpinned by phenomenology, hermeneutics and idiography. Results revealed four focus areas: general lived experiences across two worlds and how this relates to identity, what seafarers with reportedly high levels of psychological well-being experience as stressors, well-being practices of these seafarers and how these seafarers experience and make sense of mental health interventions they have come across.
Keywords: Seafaring life -- Psychological aspects; Sailors -- Mental health; Well-being; Phenomenology; Work environment